Fluoride exposure and duration and quality of sleep in a Canadian population-based sample - Jasmyn E. A. Cunningham; Hugh McCague; Ashley J. Malin; David Flora; Christine Till (Environmental Health, 2021)
Abstract Background Fluoride from dietary and environmental sources may concentrate in calcium-containing regions of the body such as the pineal gland. The pineal gland synthesizes melatonin, a hormone that regulates the sleep-wake cycle. We examined associations between fluoride exposure and sleep outcomes among older adolescents and adults in Canada. Methods We used population-based data from Cycle 3 (2012–2013) of the Canadian Health Measures Survey. Participants were aged 16 to 79 years and 32% lived in communities supplied with fluoridated municipal water. Urinary fluoride concentrations were measured in spot samples and adjusted for specific gravity (UFSG; n = 1303) and water fluoride concentrations were measured in tap water samples among those who reported drinking tap water (n = 1016). We used multinomial and ordered logistic regression analyses (using both unweighted and survey-weighted data) to examine associations of fluoride exposure with self-reported sleep outcomes, including sleep duration, frequency of sleep problems, and daytime sleepiness. Covariates included age, sex, ethnicity, body mass index, chronic health conditions, and household income. Results Median (IQR) UFSG concentration was 0.67 (0.63) mg/L. Median (IQR) water fluoride concentration was 0.58 (0.27) mg/L among participants living in communities supplied with fluoridated municipal water and 0.01 (0.06) mg/L among those living in non-fluoridated communities. A 0.5 mg/L higher water fluoride level was associated with 34% higher relative risk of reporting sleeping less than the recommended duration for age [unweighted: RRR = 1.34, 95% CI: 1.03, 1.73; p = .026]; the relative risk was higher, though less precise, using survey-weighted data [RRR = 1.96, 95% CI: 0.99, 3.87; p = .05]. UFSG was not significantly associated with sleep duration. Water fluoride and UFSG concentration were not significantly associated with frequency of sleep problems or daytime sleepiness. Conclusions Fluoride exposure may contribute to sleeping less than the recommended duration among older adolescents and adults in Canada.